Performance characterization and kinetic modeling of ozonation using a new method: ROH, O3 concept. (1st October 2017) - Kwon, Minhwan; Kye, Homin; Jung, Youmi; Yoon, Yeojoon; Kang, Joon-Wun
Abstract: Ozonation is an effective treatment for removing various organic pollutants from aquatic systems. The R ct concept, which is defined as the ratio of OH exposure to O3 exposure, has been widely used to predict the removal efficiency of target compounds, but it has significant variations by water temperature and initial O3 dose which are crucial parameters in drinking water plant. The R OH, O3 concept, which is defined as the OH exposure by O3 consumption, was proposed as a kinetic parameter for characterization and kinetic modeling for ozonation. The R OH, O3 concept is independent of temperature and initial O3 dose. A higher R OH, O3 value indicates a higher OH formation when the same amount of O3 is consumed in different water samples; therefore, the OH yield from O3 decomposition of the water samples can be compared using the R OH, O3 values. The R OH, O3 concept can also be used to characterize and model the initial ozone demand phase, and it is more convenient method compared to R ct concept. Using the R OH, O3 concept, the dynamic O3 and OH kinetics and the removal efficiencies of iopromide and ibuprofen were well predicted ( R 2 = 0.98) over a wide range of experimental conditions ( n = 124). Graphical abstract: Highlights: The R OH, O3 concept is defined as the OH exposure by O3 consumption. The R OH, O3 concept is independent of temperature and initial O3 dose. The oxidation efficiencies of the water samples can be compared using R OH, O3 concept. The ozonation performance was well predicted using R OH, O3 concept.